ANALISIS YURIDIS PEMBERIAN WAKAF ATAS TANAH YANG DIBUAT DIBAWAH TANGAN SECARA TERTULIS (STUDI PEMBERIAN WAKAF PEMBANGUNAN MESJID AL JIHAD KECAMATAN SELESAI KABUPATEN LANGKAT) - EKA FIRMAN JAYA (PREMISE LAW JURNAL, 2016)
The distribution of wakaf of a plot of land underhandedly occurred in Kwala Air Hitam, Selesai Subdistrict, precisely at Aljihad Mosque. Now it becomes a problem complained by one of the heirs of the wakif (the donor). The problems of the research were as follows: how about the legal consequence of the implementation of donating a plot of land underhandedly in a written form but it was not agreed by the heirs, how about the right and obligation of nadzir (inspector of wakaf) in the Islamic Fiqh and Law No. 41/2004 on Wakaf, how about the settlement of dispute on donating a plot of land underhandedly in a written form at Al-Jihad mosque, Selesai Subdistrict, Langkat Regency. The result of the research shows that 1) legal consequence of the implementation of donating wakaf on land underhandedly in which its status is not approved by the heir does not have any legal force because it has not been registered; therefore, nazir has to make AIW (Wakaf Oath Certificate) and/or Substituted Wakaf Oath Certificate, 2) based on the Islamic Fiqh, there is no regulation or explanation about registering wakaf land since a wakaf is valid when it has met the requirements for it. However, according to Law No. 41/2004, nazir has the responsibility to register a wakaf land in order that it has legal protection, and 3) the dispute of donating wakaf land underhandedly at Al-Jihad Mosque, Selesai Subdistrict, Langkat Regency has been settled by conducting reconciliation. Keywords: Wakaf Land, Underhanded